Role of NADPH Oxidases in Blood-Brain Barrier Disruption and Ischemic Stroke - Marina S. Hernandes; Qian Xu; Kathy K. Griendling (MDPI AG, 2022)
NADPH oxidases (Nox) are one of the main sources of reactive oxygen species (ROS) in the central nervous system (CNS). While these enzymes have been shown to be involved in physiological regulation of cerebral vascular tone, excessive ROS produced by Nox1-5 play a critical role in blood-brain barrier (BBB) dysfunction in numerous neuropathologies. Nox-derived ROS have been implicated in mediating matrix metalloprotease (MMP) activation, downregulation of junctional complexes between adjacent brain endothelial cells and brain endothelial cell apoptosis, leading to brain microvascular endothelial barrier dysfunction and consequently, increases in BBB permeability. In this review, we will highlight recent findings on the role played by these enzymes in BBB disruption induced by ischemic stroke.